Peningkatan Kualitas Bacaan Al-Qur’an Melalui Pelatihan Tajwid di Desa Pasinan - Maria Widya Wanti; Amalia Salsabilla; Khairunnisa Salsabila Putri Prameswari; Busro Muhammad Al Mursyidi; Solchan Ghozali; M. Yusron Maulana El-Yunusi; M. Hariri; Mas Ishaq Rizal; Faiq Imanuddin; Suhaidin Dena; Moh. Firman Haqiqi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to improve the quality of Qur'an reading through tajwid training in Pasinan Village. The method used is the Asset-Based Community Development (ABCD) approach, which focuses on utilizing the potential of local communities. This training was conducted for one week, with five sessions at the Pasinan Village Hall, involving children from preschool to high school age. This training includes the theory and practice of tajwid science. The results showed a significant increase in the quality of participants' Qur'an reading, which was marked by an increase in understanding of tajwid rules and increased reading skills. The main supporting factors were the enthusiasm of the participants and the harmonious cooperation between the Unsuri Team and the local community, despite the challenges in teaching early childhood children. In conclusion, this tajwid training succeeded in improving the quality of Qur'an reading in Pasinan Village and provided significant benefits to the community